The Relevance Of Islamic Educational Materials In The Prophet's Hadiths With The Concept Of Rahmatan Lil 'Alamiin's Student Profile - Anwar, Khoirul; Nurhuda, Abid; Bin Engku Ab Rahman, Engku Shahrulerizal; Al Fajri, Muhammad (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2024)
This article examines Islamic education material from the perspective of the Prophet's hadith and its relevance to the concept of the rahmatan lil alamin student profile which was initiated by the Ministry of Religion of the Republic of Indonesia in the context of implementing the independent curriculum in madrasas. Islamic education materials are materials and components prepared in the learning process according to the level and capacity of students to form a complete Muslim person. The method used is qualitative with a library research model. Then the data collection is carried out systematically to draw reliable conclusions. The results of the research show that Islamic education material is divided into five areas, namely religious education material, scientific and aqliyah education, moral education, physical education, and language education. These five Islamic education materials are also included in the hadith of the Prophet and have relevance to the student concept of rahmatan lil alamin. These include the aim of forming Islamic students who are devout, have noble character, and are moderately religious so that it has an impact on the strength of faith, the formation of commendable morals personally, towards others, nature and the state, critical and creative reasoning, integrity and discipline, and get to know and appreciate other cultures.